Governing Social Protection in the Long Term Social Policy and Employment Relations in Australia and New Zealand - Ramia, Gaby (Global Dynamics of Social Policy, 2020)
This open access book examines the comparative evolution of social protection in Australia and New Zealand from 1890 to the present day, focusing on the relationship between employment relations and social policy. Utilising longstanding and more recent developments in historical institutionalist methodology, Ramia investigates the relationship between these two policy domains in the context of social protection theory. He argues that treating employment relations as dynamic, and as inextricably intertwined with changes in the welfare state over time, allows for more accurate portrayal of similarity and difference in social protection. The book will be of most interest to researchers, advanced undergraduate and postgraduate students in social policy, employment relations, public policy, social and political history, and comparative politics.